2003
DOI: 10.1152/jn.01001.2002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Segmental and Motor Cortical Output With Contralateral Muscle Contractions and Altered Sensory Inputs in Humans

Abstract: . Changes in segmental and motor cortical output with contralateral muscle contractions and altered sensory inputs in humans. J Neurophysiol 90: 2451-2459, 2003; 10.1152/jn.01001.2002. Motor or sensory activity in one arm can affect the other arm. We tested the hypothesis that a voluntary contraction can affect the motor pathway to the contralateral homologous muscle and investigated whether alterations in sensory input might mediate such effects. Responses to transcranial magnetic stimulation [motor-evoked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
205
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(227 citation statements)
references
References 48 publications
19
205
2
1
Order By: Relevance
“…Imaging studies indicate that motor centers in both cerebral hemispheres are active during unilateral muscle contraction (7,9,17,19), and studies involving transcranial magnetic stimulation (TMS) demonstrate that ipsilateral motor cortex excitability is suppressed by weak unilateral contractions (22,23,37) and that it is facilitated by high-force contractions (13,14,38). Strong ipsilateral contractions also depress intracortical inhibition (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging studies indicate that motor centers in both cerebral hemispheres are active during unilateral muscle contraction (7,9,17,19), and studies involving transcranial magnetic stimulation (TMS) demonstrate that ipsilateral motor cortex excitability is suppressed by weak unilateral contractions (22,23,37) and that it is facilitated by high-force contractions (13,14,38). Strong ipsilateral contractions also depress intracortical inhibition (25).…”
mentioning
confidence: 99%
“…Importantly, the scale of these ipsilateral cortical effects is proportional to force production: the greater the force of unilateral contraction, the larger the effect on the opposite hemisphere (9, 14, 25). At a segmental level, movements performed with one limb typically result in depression of the central gain of the Ia afferent reflex pathway (4,6,14). There are also crossed interactions between inhibitory interneurons that receive inputs from primary muscle afferents (8,16, 34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Munn et al (2005) explained that muscular training on one side of the body can enhance the muscular power of the limbs on the other side because it involves more motor units and the activation increases in the central nervous system 15) . Similarly, Hortobagyi et al (2003) and Kristeva et al (1991) reported that the cross-training effect is controlled at the cortical level; they explained that the cross-training effect occurs as the sensory motor faculty of both sides becomes active 18,19) . The cross-training effect is applied in PNF training to promote muscular power of the weak side and has proven effective.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the cross facilitation phenomenon is related to the propagation of neural signals between the left and right hemispheres in both brain level as in spinal level 25 . Some researchers have demonstrated voluntary contraction of upper limb muscle may enhance the action of the contralateral homologous muscle 26,27 , for example, voluntary contraction of right biceps brachial increase the action of left biceps. However, to the best of our knowledge, this is the first study investigating the effects on non-homologous muscle performance (e.g., biceps and triceps).…”
Section: Discussionmentioning
confidence: 99%